The prevalence of occupational stress amongst general practitioner in Ampang, Selangor - Shamsul lkhwan Ashari Azmi,; Noor Hassim Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
This cross-sectional study was conducted among general practitioners in Ampang, Selangor between November 1998 and March 1999. Sample population was 70 general practitioners from 30 clinics which were chosen. The objective of this study was to determine the prevalence of occupational stress among general practitioners. This study applied self-administered questionnaires, which were structured to consist of questions on socio-demography, occupational history and symptoms of stress. Symptoms of stress were based on Personal Stress Inventory, which uses 52 questions to determine stress levels. The response rate was 64.3% and the prevalence of occupational stress was 32.5%. The main stress symptoms among stressed general practitioners were symptoms of tension (92.9%) and gastrointestinal symptoms (86.7%). It can be concluded that general practitioners are experiencing occupational stress and this could be anticipated from the frequency of the symptoms being present. Steps to recognize symptoms of stress should be taken by both the management and the general practitioners in order to enable preventive measures to be taken to ameliorate their working environment.